Analisis Pelaksanaan Komunikasi Terapeutik Perawat di Ruang Rawat Inap RS Pemerintah dan RS Swasta - Nova Fitria; Zahroh Shaluhiyah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2017)
Background: Equality role of government hospitals and private hospitals in improving the quality of health services in Indonesia, causing every hospital should provide a good service and quality. Nurses are part of hospital human resource that considerable influence on the quality of service, and the implementation of good nursing care can not be separated from therapeutic communication, then the optimal implementation of therapeutic communication by nurse is one of the efforts to improve services to the patients.Method: The type of this research was quantitative analytical, with a design using cross-sectional study.Results: The results showed a significant differences in the implementation of nurses therapeutic communication between public hospitals and private hospitals, where the implementation of nurses therapeutic communication in private hospital are better. Associated factors significantly with the implementation of nurses therapeutic communication in public hospitals and in private hospitals are the same, the variables are job satisfaction, work motivation, work climate, coworkers support and head of ward support. The most dominant factor that affects the compliance of nurses in government hospitals in implementing therapeutic communication is work motivation (OR 36.866), while in private hospitals is head of ward support (OR 28.598). Significant differences between the government hospitals and private hospitals appears on variables : age, period of work, attitude, job satisfaction, work motivation, work climate, coworker support , head of ward support, and the implementation of therapeutic communication itself. Keywords: Implementation, Therapeutic Communication, Government-Private Hospital